2010
DOI: 10.1016/j.bbadis.2010.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-6 trans-signaling in CCl4 induced liver damage

Abstract: Interleukin-6 (IL-6) plays an important role in liver regeneration and protection against liver damage. In addition to IL-6 classic signaling via membrane bound receptor (mIL-6R), IL-6 signaling can also be mediated by soluble IL-6R (sIL-6R) thereby activating cells that do not express membrane bound IL-6R. This process has been named trans-signaling. IL-6 trans-signaling has been demonstrated to operate during liver regeneration. We have developed methods to specifically block or mimic IL-6 trans-signaling. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…IL-6 also binds to both membrane-bound IL-6 receptor and soluble IL-6 receptor to trigger NF-κB- and STAT3-dependent hepatic regeneration [36, 37]. TGF-β 1 is mainly a pro-fibrotic factor in chronic liver disease, e.g., fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 also binds to both membrane-bound IL-6 receptor and soluble IL-6 receptor to trigger NF-κB- and STAT3-dependent hepatic regeneration [36, 37]. TGF-β 1 is mainly a pro-fibrotic factor in chronic liver disease, e.g., fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aldeguer et al characterized a paracrine mechanism by which cells of bone marrow origin, most likely Kupffer cells, regulated the regenerative capacity of hepatocytes through IL-6 expression [29]. Gewiese-Rabsch et al demonstrated that IL-6 trans-signaling via soluble IL-6R was important for the physiological response of the liver to CCl4-induced chemical damage [26]. Kawasaki et al reported that platelets promoted liver-specific endothelium cell proliferation and induced IL-6 and vascular endothelial growth factor production.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the findings of focal hepatocyte necrosis surrounded by either hemorrhages or inflammatory infiltrates in the patients were considered as direct histological evidence of drug toxicity related to the tocilizumab and anakinra. It has been suggested that the hepatic necrosis due to anakinra is a T-cell-dependent apoptotic immune-mediated response 9,10…”
Section: Discussionmentioning
confidence: 99%